Matter of time : the transitivity of the verbs in sculpture making. - Tay, In Ing. (2011)
Inspired by Richard Serra’s manipulation of lead, Matter of Time is an ongoing study on such transitive verbs as - “to absorb, to drip, to leak, to spill.” - together with nouns pointing out the liquid component of my sculpture. The focus lies in the chosen materials, epoxy resin and soil as the main ingredients to illustrate the process of these actions.